Morita–Baylis–Hillman reaction of a chiral aziridine aldehyde. Issue 43 (5th September 2018) - Lee, Jaedeok; Singh, Deepak; Ha, Hyun-Joon
Abstract : The Morita–Baylis–Hillman reaction of chiral aziridine-2-carbaldehyde with alkyl acrylate was carried out under various conditions by changing bases and alcohol additives. Abstract : The Morita–Baylis–Hillman reaction of ( R )-1-(( R )-1-phenylethyl)aziridine-2-carbaldehyde with alkyl acrylate was carried out under various conditions by changing solvents, bases, and alcohol additives. The reaction at room temperature under neat conditions (no solvent) with quinuclidine as an amine nucleophile, in the presence of benzyl alcohol as an additive, afforded a product, γ-(aziridin-2-yl)-β-hydroxy-α-methylene butanoate, in 97% yield with a diastereomeric ratio of anti and syn as 86 : 14.